Effect of Water-Cement Ratio on the Macrocell Polarization Behavior of Reinforcing Steel - Zhonglu Cao; Makoto Hibino; Hiroki Goda (Journal of Engineering)
The effect of water-cement ratio on the macrocell polarization behavior of reinforcing steel embedded in cement mortars was investigated by comparing and analyzing the macrocell polarization ratios and slopes of anodic and cathodic steels. Based on the experimental results, the relationship between macrocell potential difference and macrocell current density was also analyzed, and the mechanism of macrocell polarization affected by water-cement ratio was proposed. The results indicated that the water-cement ratios had little impact on the macrocell polarization ratios of cathode and anode. The lower water-cement ratio could reduce the macrocell current by decreasing the macrocell potential difference and increasing the macrocell polarization resistance of the cathode and anode.